The Effectiveness of Formative and Summative Assessments in Improving the Achievement of Aqidah and Akhlak Learning at MA Islamiyah - Ahmad Muthi’Uddin; Mauli Mamba’us Shofy; Fahmi Khumaini (Values: Jurnal Kajian Islam Multidisiplin, 2025)
Aqidah akhlak is an education that is very much needed by students, so that it can reflect and instill noble morals in the souls of children during their growth. The most important supporting factor for the success of student learning outcomes is the use of good formative and summative assessments. The better the use of formative and summative assessments, the better the learning outcomes of aqidah akhlak for students. This study was conducted at MA Islamiyah Senori school, using a quantitative approach of the correlational quantitative type. The data collection method used by this researcher was the distribution of questionnaires, with the research subjects being class X students with a population of 173 and the sample technique was taken using the systematic sampling technique, there were 32 students used as research samples. Based on the results of the Product moment correlation hypothesis test data, it is known that the Pearson Correlation value of 0.744> rtable value of 0.349 and the Sig value, (2-tailed) 0.00 <0.05, it can be seen that H_a is accepted and H_o is rejected, if the Pearson Correlation value is smaller than rtable and the Sig value, (2-tailed) is greater than 0.05 then H_(o) is accepted and H_a is rejected. So it can be concluded that variable X is significantly related to variable Y. This means that there is an influence of the use of formative and summative assessments in efforts to improve the learning outcomes of aqidah akhlak class X MA Islamiyah Senori